If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1y = 31 Solving 3x + 1y = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + 1y + -1y = 31 + -1y Combine like terms: 1y + -1y = 0 3x + 0 = 31 + -1y 3x = 31 + -1y Divide each side by '3'. x = 10.33333333 + -0.3333333333y Simplifying x = 10.33333333 + -0.3333333333y
| 5x^2+9x-20=0 | | V-5=7 | | -5x^2-9x+28=0 | | 5x-1+6x=3 | | (5y/4c^3k^2)+(k^3w/8c^2d) | | 1/3(d-4)-3/2(5d-3)=5/6 | | x=-16+4 | | 0.5=4(5x-3) | | 8x+5+7x-12=10x+113 | | log(4)(1/64) | | 9y-7.7=4.5 | | 4x^2-20=-5x^2-6x-5 | | 2y-98=0 | | y=2x^2-8x+2 | | 32=((3w-9)/2)+((9w-4)/4) | | (4x)/(7)=(28)(7) | | 32=(3w-9)/2+(9w-4)/4 | | 32=(3w-9/2)+(9w-4)/4 | | 7x-8=7-2x | | 100=(750-x)/x | | 4y^2=-7y-3 | | 100x+x=750 | | (2x+4)3=-4 | | 3x^2+8=14x | | 4r-8+y=3 | | (1/2x+2)+(1/4x-3)=2 | | (1/(2x+2))+(1/(4x-3))=2 | | 6x-1=2(2x+2)(4x-3) | | 16x^2+2x-11=0 | | 2-2=4x | | 16x^2-2x-11=0 | | a^2-1100a=-57939.16 |